Fresh State and Mechanical Properties of Lithium Slag Green Concrete - Rahman, Sm Arifur (Curtin University, 2024)
This thesis explores using lithium slag (LS) from battery production as a supplementary cementitious material (SCM) in concrete to address environmental and economic challenges. The LS is found to enhance concrete properties and reduce carbon footprint. The 40% LS as a SCM improves long-term strength, workability, and microstructure of concretes, making it a viable option for green concrete. LS is effective in 3D concrete printing with added fibres and highlighting its potential for sustainable construction.